Works of Art in the Reign of King Prajadhipok - Suteerangkul, Paweena (Journal of the Faculty of Arts, Silpakorn University, 2020)
This qualitative research aims to collect artworks and also analyze their historic background and artistic style in King Prajadhipok’s reign. Under the influence of Western art, paintings and sculptures created by Thai artists during the year 1925-1934 were studied by analyzing document papers and conducting in-depth interviews with experts. The study shows that 1) the artworks found during this era include mural paintings, portrait paintings, landscape paintings, drawings, illustrations, monuments, portrait sculptures and commemorative medals; and 2) most of the artworks during this era were mainly created to serve the royal court, while some partially belonged to the artists themselves. The characteristics of the artworks in this era under Western art influence could be divided into two groups: traditional Thai artworks with Western influences and Western style artworks. Every art piece imitates the realness of anatomy, perspective, coloring, light and shadow; however, they are different in Western-influenced proportions.